As contribuições da ludicidade no processo de apropriação do sistema de escrita alfabética: relato de uma experiência do projeto de extensão da Universidade Federal do Amazonas - Clemente, Ana Vitória da Silva (Brasil, 2024)
The article aims to present the theoretical and methodological refer- ences of one of the actions developed in the extension project of the Federal University of Amazonas in partnership with a school in the Amazonas state network in the city of Manaus called “Itinerant Literacy: from network to network on the trails of words”, aiming to reflect on pedagogical practices aimed at appropriating the alphabetic writing system through playful games in order to promote curiosity, motivation and enchantment in learning to read and write.